Association between visual impairment and body mass index in students from rural China - Hongyu Guan; Zhijie Wang; Yuxiu Ding; Yunyun Zhang; Kang Du; Yaojiang Shi (Singapore Medical Journal)
Introduction: Visual impairment and obesity remain the major public health issues among school-age students in rural areas of China. Obesity is an underlying risk of vision problems. This study aimed to assess the association between visual impairment and body mass index (BMI) among school-age students in rural northwest China. Methods: This study included 39,385 students from the 4th to 9th grade in rural northwest China. From 2018 to 2020, students underwent an assessment of visual acuity (VA) and completed a questionnaire on family demographics, and height and weight measurements. Multiple logistic regression analyses were used to analyse the data. Results: The association between visual impairment and BMI groups was significant in the study population (P = 0.002) and in different groups (at the different educational, provincial and national levels) (P < 0.001, separately). Multiple logistic regression analyses revealed a positive relationship between visual impairment and obesity in the study population, including those attending primary school, Han students and the residents of Ningxia autonomous region. Conclusion: The association between visual impairment and obesity was significant among school-age students in rural northwest China. There should be implementation of policies to address the problem about visual impairment and obesity among school-age students in rural areas.